2022
DOI: 10.1186/s12936-022-04310-7
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of malaria and its risk factors in Lake Tana and surrounding areas, northwest Ethiopia

Abstract: Background In Ethiopia, malaria is a major concern to the health, and socio-economic development of the country because of its occurrence at the peak agricultural activities. Factors such as environmental, human host, parasite, and vector determine malaria transmission. Therefore, the present study was conducted to determine the prevalence and associated factors of malaria among febrile patients who visited selected health centres. Methods Institut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
2
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 54 publications
1
2
1
Order By: Relevance
“…This disparity could be attributed to differences in study design and setting; for example, the study in Ibadan, Nigeria, was done in health facilities, which may have overestimated the prevalence compared to a community‐based study. In contrary to this, the prevalence of symptomatic malaria in this study was higher than reported in Ziquala district, Northeast Ethiopia (24.6%), 44 Lake Tana and its surrounding areas, Northwest Ethiopia 24.7%, 45 the Mount Cameroon area (41.7%), 46 the Pakro subdistrict of Ghana 32.9%, 47 and Dzanga Sangha Region, Central African Republic (35.2%) 48 and Malawi (19.0%) 49 . This variation might be attributed to the different data collection periods, settings, laboratory method, and laboratory personnel skills.…”
Section: Discussioncontrasting
confidence: 99%
“…This disparity could be attributed to differences in study design and setting; for example, the study in Ibadan, Nigeria, was done in health facilities, which may have overestimated the prevalence compared to a community‐based study. In contrary to this, the prevalence of symptomatic malaria in this study was higher than reported in Ziquala district, Northeast Ethiopia (24.6%), 44 Lake Tana and its surrounding areas, Northwest Ethiopia 24.7%, 45 the Mount Cameroon area (41.7%), 46 the Pakro subdistrict of Ghana 32.9%, 47 and Dzanga Sangha Region, Central African Republic (35.2%) 48 and Malawi (19.0%) 49 . This variation might be attributed to the different data collection periods, settings, laboratory method, and laboratory personnel skills.…”
Section: Discussioncontrasting
confidence: 99%
“…Utilization of LLIN was a significant protective factor against malaria infection in this study. This is in agreement with previous studies in Ethiopia [ 25 , 56 ]. This is because LLIN either mechanically inhibits mosquitoes from biting or biologically kills mosquitoes that come into contact with it [ 57 ].…”
Section: Discussionsupporting
confidence: 94%
“…This is inconsistent with the report of the WHO, which reported that P. falciparum is the dominant parasite in many parts of Ethiopia [ 3 ]. The dominance of P. falciparum was described in multiple studies conducted across Ethiopia [ 25 , 27 , 28 ]. However, reports showed that P. vivax was the dominant cause of malaria in various parts of Ethiopia [ 29 , 37 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Evidence from increased malaria infection among children living in houses with mosquito entry opening holes on the their walls is in line with other similar studies, such as (23)(24)(25)(26). Several structural de ciencies on houses that could allow entry of mosquitoes were found such as lack of screening, and external doors not tting perfectly into walls hence potential for mosquito entry at night (27).…”
Section: Discussionsupporting
confidence: 91%
“…Improving house structure is known to limit contact between humans and mosquitoes, and hence, reduces risk of malaria transmission. Our study indicated that several house characteristics such as, the presence of holes on walls, opened eaves, unscreened window and living close to breeding sites, favored mosquito presence in houses (24,25,29).…”
Section: Discussionmentioning
confidence: 70%